Identifying misconceptions in students’ understanding of the concept of physical and chemical change with open-ended questions - Fitriani, Linda; Syafawani Ridho, Yusro; Indra Pratiwi, Maya; Widi Wisudawati, Asih (Universitas Papua, Manokwari, Indonesia, 2025)
This study aims to identify misconceptions in students’ understanding of physical and chemical changes using objective instruments in the form of open-ended descriptions and reasons. Chemistry is a science that underlies knowledge of the structure and changes of matter through three levels of representation: macroscopic, submicroscopic, and symbolic. However, students’ limited ability to connect these levels of representation often leads to misconceptions that can hinder understanding of more complex concepts in the future. This study used a qualitative descriptive approach with 21 grade 10 students at a high school in Yogyakarta as subjects. The research instrument consisted of 5 open-ended questions and reasons used to categorize students’ mindsets into understanding the concept, misconceptions, and not understanding the concept. The study found misconceptions across various subconcepts, including the assumption that chemical changes are absolutely unidirectional (irreversible) and the inability to distinguish particle interactions during salt dissolution and magnesium combustion. The main factors causing these misconceptions are incomplete preconceptions, incorrect reasoning, and a lack of in-depth understanding at the submicroscopic level. This placement emphasizes strengthening knowledge of basic concepts and integrating levels of chemical representation to improve students’ thinking patterns.